2020
DOI: 10.1108/jcs-04-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Children witnessing domestic violence

Abstract: Purpose Witnessing domestic violence is a common experience among children, but has only recently been recognized as a specific form of abuse. The purpose of this paper is to present a review of the researchers who have examined the experience of children witnessing domestic violence. Design/methodology/approach Research papers related to witnessing domestic violence and published in leading academic journals in the UK and abroad from January 1980 to September 2018 were identified and reviewed. Findings Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
8
0
3
Order By: Relevance
“…Ebeveynlerin mevcut kaynakları üzerindeki dengesizliği artıran herhangi bir sosyodemografik, ailevi veya kişisel özellik ebeveyn tükenmişliğine yönelik savunmasızlığı artırmada rol oynamaktadır (Roskam vd., 2017) (Dodaj, 2020). Aile içi şiddetin kadınlar ve çocukların ruh sağlığı üzerindeki etkilerinin bilinmesi oldukça önemlidir (Almiş, Gümüştaş ve Koyuncu Kütük, 2020).…”
Section: Toplum Ve Sosyal Hizmetunclassified
See 2 more Smart Citations
“…Ebeveynlerin mevcut kaynakları üzerindeki dengesizliği artıran herhangi bir sosyodemografik, ailevi veya kişisel özellik ebeveyn tükenmişliğine yönelik savunmasızlığı artırmada rol oynamaktadır (Roskam vd., 2017) (Dodaj, 2020). Aile içi şiddetin kadınlar ve çocukların ruh sağlığı üzerindeki etkilerinin bilinmesi oldukça önemlidir (Almiş, Gümüştaş ve Koyuncu Kütük, 2020).…”
Section: Toplum Ve Sosyal Hizmetunclassified
“…İlaveten çalışmada aile içi şiddete tanık olmanın çocukların bilişsel, fiziksel, psikolojik ve davranışsal işlevsellik gibi alanlarda çocuğun gelişiminde kısa ve uzun vadeli birçok olumsuz sonuçlarla ilişkilendirildiği belirtilmiştir. Dodaj (2020) çalışmasında ayrıca ebeveyn/bakım veren kişilerin sahip oldukları düşük eğitim düzeyi, sosyoekonomik statü, tek ebeveynlik, psikolojik zorlukların yaygınlığı ve güvensiz bağlanma stillerini de çocukların aile içi şiddete maruz kalma riskini açıklayan risk etmenleri olarak belirtilmiştir.…”
Section: Toplum Ve Sosyal Hizmetunclassified
See 1 more Smart Citation
“…In addition, children who have witnessed physical domestic and family violence have been excluded from previous pooled estimates. However, evidence from individual studies suggest that girls are more likely than boys to witness physical violence between family and household members ( Dodaj, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…13 Violence in the form of disciplinary measures is repeatedly used by caregivers of almost 1 in 7 of the world's children aged 2 -4 years. 14 Although it is difficult to measure exactly how many children experience emotional abuse, available evidence shows that worldwide, 1 in 3 children are estimated to have suffered some form of nonphysical degrading behaviour or attitude. 15 Moreover, examinations of global patterns of violence against children have demonstrated that 1 in 4 children live with a mother who is in an abusive relationship.…”
mentioning
confidence: 99%